Epidemiological Characterization of Avian Salmonella enterica Serovar Infections in India - Prakash, B.; Krishnappa, G.; Muniyappa, L.; Kumar, B. Santhosh (International Journal of Poultry Science, 2005)
The study was undertaken to elucidate the recent epidemiological status of salmonellosis in India. A total of 23 Salmonella isolates were recovered from different disease outbreaks in different geographical locations. The phenotypic analysis by serotyping, transmission electron microscopy and antibiogram profiles were able to classify the Salmonella isolates based on different serovars. The S. Gallinarum isolates were also classified into different strains based on the resistance pattern to different antimicrobials used. The plasmid profiles of the Salmonella isolates were also found to be serovar specific and the S. Gallinarum isolates were subdivided into different strains based on the geographical origin. There was a positive correlation between the antibiotic resistance pattern and the presence of plasmid within different serovars.